Pattern generation for delay testing and dynamic timing analysis considering power-supply noise effects. - Krstic, A. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Noise effects such as power supply and crosstalk noise can significantly impact the performance of deep submicrometer designs. Existing delay testing and timing analysis techniques cannot capture the effects of noise on the signal/cell delays. Therefore, these techniques cannot capture the worst case timing scenarios and the predicted circuit performance might not reflect the worst case circuit delay. More accurate and efficient timing analysis and delay testing strategies need to be developed to predict and guarantee the performance of deep submicrometer designs. In this paper, we propose a new pattern generation technique for delay testing and dynamic timing analysis that can take into account the impact of the power supply noise on the signal propagation delays. In addition to sensitizing the selected paths, the new patterns also cause high power supply noise on the nodes in these paths. Thus, they also cause longer propagation delays for the nodes along the paths. Our experimental results on benchmark circuits show that the new patterns produce significantly longer delays on the selected paths compared to the patterns derived using existing pattern generation methods